Case Report: Splenic Ischemia Induced by Volvulus of Ileum - Sergi, Mauro; Chisari, Giulia; Lombardo, Sofia Paolo; Fontana, Paolo (Frontiers in Surgery, 2022)
A 31- year-old female patient was admitted to the emergency department with signs and symptoms of acute abdomen. Urgent CT scan was performed and small bowel volvulus, with whirlpool sign, was noted and torsion of the spleen was also involved too.